Direct Oral Anticoagulants Versus Warfarin in the Treatment of Left Ventricular Thrombus. Issue 7 (July 2021) - Willeford, Andrew; Zhu, Wenhong; Stevens, Craig; Thomas, Isac C.
Background: Use of direct oral anticoagulants (DOACs) for the treatment of left ventricular (LV) thrombus has gained considerable interest. Objective: We aimed to evaluate if DOACs are effective in the treatment of LV thrombus compared with warfarin. Methods: We evaluated the medical records of patients diagnosed with a new LV thrombus at a tertiary medical center. The primary outcome was the composite of thrombus persistence, stroke, or systemic embolism. We adjusted for potential confounders using multiple logistic regression. The safety outcome was the composite of hemorrhagic stroke or bleeding requiring blood transfusion. Results: A total of 129 patients were treated with warfarin and 22, with a DOAC. In unadjusted analysis, 54.3% of patients treated with warfarin met criteria for the efficacy outcome as compared with 40.9% of patients treated with a DOAC ( P = 0.25). In adjusted analysis, no difference between groups was observed (odds ratio = 0.39; 95% CI = 0.14-1.06; P = 0.07 for DOAC vs warfarin). In all, 3.9% of patients treated with warfarin met safety criteria as compared with 4.5% of patients treated with a DOAC. A total of 8 patients in the warfarin group had a stroke or systemic embolism as compared with 0 patients in the DOAC group ( P = 0.37). Conclusion and Relevance: Our data suggest that DOACs may be reasonable alternatives for treatment of LV thrombus. When added to the totality of available studies, this study demonstrates that the effectiveness of DOACs in LV thrombus remains uncertain. Randomized clinical trials are needed.